Adaptation to climate change and impact on smallholder farmers' food security in South Africa - Ogundeji, Abiodun A. (MDPI, 2022)
If not adequately managed, climate change is predicted to have a large negative impact on smallholder subsistence farmers, posing a significant danger to household food security. However, the role of adaptive techniques used by farming households to reduce these negative effects and, as a result, their food insecurity status has not been sufficiently evaluated. This study explores the factors that influence smallholder farmers’ adoption of climate change adaptation measures, as well as their impact on household food security. Using an endogenous treatment-effect ordered probit model, agricultural households’ food security status is likely to significantly improve when they employ measures to adapt to adverse climatic conditions. The empirical findings also show that the gender makeup of the household, age, tropical livestock unit, and access to climatic information improve the likelihood of smallholder farmers adopting climate change adaptation measures. Based on the findings, this study advocates that governments and non-governmental organizations (NGOs) support smallholder farmers’ Indigenous adaptation options with various institutional, regulatory, and technological assistance, with a particular emphasis on female-headed households.
Keywords: Food security; Climate change; Adaptation strategies; Treatment-effect ordered probit